FENOMENA GEGAR BUDAYA (CULTURE SHOCK) PADA MAHASISWA BIPA DARI KOREA SELATAN DI LBI UNIVERSITAS INDONESIA - Faradella, Keke (Istek Widuri Jakarta, 2023)
Living in a new environment in Indonesia is considered foreign by BIPA’s Students from South Korea at LBI University of Indonesia become a description of the phenomenon cultural shock occurred in Indonesia because of the many differences that exist between the two countries. The purpose of this study is to determine the phases, causes, symptoms or reactions of the cultural shock experienced by BIPA’s Students from South Korea. The results showed that BIPA’s Students from South Korea at the beginning of their arrival to Indonesia experienced a cultural shock. They experience four phases of a cultural shock, a phase of excitement, a phase of disappointment, an early phase of resolution and an effective functioning phase. The cause of cultural shocks that occurred at the students of BIPA LBI UI from South Korea are the main in terms of the language of weather or climate and daily habits. The phenomenon or reaction of culture shock happened to BIPA LBI UI students from South Korea such as feeling lonely, bored, confused, stressed, home sick, lack of confidence, to experience physical pain.